Pengaruh Konsentrasi Asam Stearat dan Lama Pengadukan Proses Gelatinisasi terhadap Karakteristik Komposit Bioplastik Maizena-Glukomanan - Haloho, Reksi Julnigo; Hasojuwono, Bambang Admadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p06, 2021)
This study aims to determine the effect of stearic acid concentration and the stirring time and also the interaction of both on the characteristic of the cornstarch-glucomannan bioplastic composite and also to determine the cornstarch-glucomannan bioplastic composite on the concentration of stearic acid and stirring time produce the best characteristic. The research used a factorial randomized block design. The first factor is the concentration of stearic acid consisting of 4 levels that is 0.1%; 0.2%; 0.3%; 0.4% (w/w). The second factor is stirring time consisting of 4 levels that are 3, 4, 5, 6 minutes. The observed variable on this study were tensile strength, elongation at break, modulus young, swelling, water vapour transmission rate (WVTR), biodegradation, and functional group profile. The data were analyzed of variant and continued with Duncan Multiple Range Test (DMRT). The result of this study indicate that the concentration of stearic acid and stirring time of gelatinization process has a very significant effect on the tensile strength, modulus young, swelling, water vapour transmission rate (WVTR), biodegradation, but the concentration of stearic acid had no significant effect on elongation at break. The interaction between treatments has a very significant effect on elongation at break. Concentration stearic acid 0.4% and stirring time 6 minutes treatment resulted in the best bioplastic composite with a tensile strength 22.17 MPa, elongation at break 8.55%, modulus young 260.87 MPa, swelling 81.58%, water vapour transmission rate 0.638 g/m 2 .hour and biodegradability 7 days. The composite of cornstarch-glucomannan and stearic acid consists of hydroxyl (O-H), carboxyl (C-O), carbonyl (C=O), and hydrocarbon (CH 2 )n . Keywords : bioplastic, cornstarch, glucomannan, stearic acid, stirring time